1999
DOI: 10.1002/j.1556-6978.1999.tb00568.x
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Counselor Supervisor Nondisclosure

Abstract: This study examined the types of information counselor supervisors do not disclose to their trainees. Results from a national sample of 90 supervisors indicated that their nondisclosures fell into 12 categories, and that there were 9 reasons associated with these 12 types of nondisclosures.A primary role of counselor supervisors is to provide feedback to their trainees to enhance their learning and competence (Bernard & Goodyear, 1992;Blocher, 1983;Holloway, 1992). Because feedback could be limitless, yet time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
45
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 20 publications
(24 reference statements)
2
45
0
Order By: Relevance
“…Yourman (2003) also discussed anecdotal evidence that SRSD may ease supervisee shame and, therefore, increase a supervisee's willingness to self-disclose. Furthermore, research informed by supervisees' reports has demonstrated that when supervisors and supervisees did not self-disclose, communication was impeded, potentially imperiling the supervisory working alliance and supervisees' clinical work and development (Hess et al, in press;Ladany et al, 1996;Ladany & Melincoff, 1999). Ladany and Lehrman-Waterman (1999) also noted a relationship between SRSD and the working alliance: The greater the number of self-disclosures perceived by the supervisee, the stronger the supervisee perceived the supervisory working alliance.…”
Section: Supervisor Self-disclosurementioning
confidence: 99%
See 4 more Smart Citations
“…Yourman (2003) also discussed anecdotal evidence that SRSD may ease supervisee shame and, therefore, increase a supervisee's willingness to self-disclose. Furthermore, research informed by supervisees' reports has demonstrated that when supervisors and supervisees did not self-disclose, communication was impeded, potentially imperiling the supervisory working alliance and supervisees' clinical work and development (Hess et al, in press;Ladany et al, 1996;Ladany & Melincoff, 1999). Ladany and Lehrman-Waterman (1999) also noted a relationship between SRSD and the working alliance: The greater the number of self-disclosures perceived by the supervisee, the stronger the supervisee perceived the supervisory working alliance.…”
Section: Supervisor Self-disclosurementioning
confidence: 99%
“…Two of the findings (i.e., to enhance the supervision relationship, to model supervisee disclosure) provide empirical support for those theorized by Farber (2006) and thereby invite additional research to see whether they also emerge in other investigations. Participants' reasons for refraining from SRSD echo those found by Ladany and Melincoff (1999), suggesting that if supervisors fear that the SRSD is irrelevant to supervision or connects too closely to the supervisor's personal concerns, or if supervisees are not ready to hear or will react negatively to the SRSD, prudence may dictate that such SRSDs not be offered. Finally, the types of SRSDs reported by our participants mirror those found in the literature (Ladany & Lehrman-Waterman, 1999).…”
mentioning
confidence: 90%
See 3 more Smart Citations